Surgical research in the north and northeast of Brazil - Araújo,Rafael Silva de (2013)
PURPOSE: To evaluate the scientific production from the surgical areas from the State University of Para (UEPA), Federal Universities of Para (UFPA) and of Paraiba (UFPB), Brazil. METHODS: The scientific productions of professors in the last five years were classified according to the Qualis system of CAPES-Medicine III (http://qualis.capes.gov.br/webqualis/publico/pesquisaPublicaClassificacao.seam?conversationPropagation=begin) and it was computed the number of guidance of students scientific projects. RESULTS: Seventy-four professors were included, 31 with Master and 43 with PhD degrees. UFPA presented more publications (49% out of the total), which 32% of them in Journals B1 or higher. Otorhinolaryngology presented the greatest number of publications (29% out of the total); however, 98% of them in B3 or lower. Gastroenterological Surgery, which is responsible for 23% out of the total, had 57% of its publications in B1 or higher. The most frequent type of guidance was the one about scientific work of completion of undergraduate course (63%). Gynecology and Obstetrics presented the greatest number of student's guidance (35% out of the total) and Gastroenterological Surgery the largest number of Master's degree and PhD degree supervisions. CONCLUSIONS: The specialties Gynecology and Obstetrics and Gastroenterological Surgery from the State University of Para (UEPA), Federal Universities of Para (UFPA) and of Paraiba (UFPB) presented the greatest number of professors with academic degrees. Gastroenterological Surgery presented the largest scientific productions at higher strata of WebQualis CAPES classification and also the largest number of Master and PhD directed.